2018
DOI: 10.1590/0102-311x00012818
|View full text |Cite
|
Sign up to set email alerts
|

Homicides and socio-environmental determinants of health in Brazil: a systematic literature review

Abstract: Brazil currently has the highest absolute number of homicides in the world, which results from a complex range of factors. This study aimed at understanding the associations between socio-environmental determinants of health (SDH) and homicides in Brazil through a systematic literature review. The review followed PRISMA guidelines, selecting quantitative and qualitative studies published in Portuguese, English, and Spanish carried out between 2002 and 2017, available in the PubMed, MEDLINE, LILACS, SciELO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 60 publications
0
24
0
11
Order By: Relevance
“…Previous research has found similar effects in other South American countries. For instance, a study on homicide and youth in the state of Santa Catarina and Paraná in Paraguay showed an increase in homicide rate in the cities located on country borders and those close to highways that connect major cities in South and South East regions of Brazil and Paraguay (Wanzinack et al 2018 ). Furthermore, the North, Northeast, and Central regions of Brazil which are agricultural frontiers with land tenure-related conflicts have the highest homicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found similar effects in other South American countries. For instance, a study on homicide and youth in the state of Santa Catarina and Paraná in Paraguay showed an increase in homicide rate in the cities located on country borders and those close to highways that connect major cities in South and South East regions of Brazil and Paraguay (Wanzinack et al 2018 ). Furthermore, the North, Northeast, and Central regions of Brazil which are agricultural frontiers with land tenure-related conflicts have the highest homicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…Another 26% of the victims had their deaths associated with passive or active actions in criminal activities. The victimization of women by homicide linked to urban violence appears not to be exclusive to Manaus and is relatively common in other large Brazilian cities like Porto Alegre (Rio Grande do Sul State) and Recife (Pernambuco State), among others 28,29,30,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Os homicídios de mulheres estão fortemente associados à violência praticada pelo parceiro íntimo e as relações de gênero desiguais que acabam culminando no domínio dos homens sobre o corpo e a vida de suas parceiras, representando a cultura da hegemonia, agressividade e do machismo (Wanzinack et al, 2018).…”
Section: Discussionunclassified
“…A cada duas horas uma mulher é assassinada no Brasil e por isso o país ocupa o 12º lugar do ranking mundial de homicídios de mulheres (Wanzinack, Signorelli, & Reis, 2018).…”
Section: Introductionunclassified